Effect of Cooling Rate on Properties of Beeswax and Stearic Acid Oleogel Based on Rice Bran Oil and and Sesame Oil - Sivakanthan, S.; Fawzia, S.; Mundree, S.; Madhujith, T.; Karim, A. (MDPI, 2024)
This study aimed to investigate how varying cooling rate impacts the characteristics of oleogels prepared using a sesame oil and rice bran oil blend (5:6, w/w) using a combination of beeswax and stearic acid (3:1, w/w at 12%, w/w) as the oleogelators. The study assessed three different cooling rates—0.5, 1.5, and 5 °C/min—with a focus on the attributes of the oleogels. The study revealed that the cooling rate had a substantial impact on the strength of the gel network. The cooling rate of 0.5 °C/min resulted in a higher oil-binding capacity and a stronger gel structure than fast cooling. The thermal properties and molecular interactions of the oleogels were not influenced by the cooling rate. The findings of this study indicated that the characteristics of beeswax and stearic acid oleogel prepared using sesame oil and rice bran oil blend could be tailored by manipulating the cooling rate.
Keywords: Oil binding; Oleogelation; Rheology; Saturated fat; Structured lipid; Trans fat